Preparation method of conductor rubbing nanogenerator and application thereof

CN115549515BActive Publication Date: 2026-10-27NANJING TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211265470.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-17
Publication Date
2026-10-27
Estimated Expiration
2042-10-17

AI Technical Summary

Technical Problem

然而,设计出能够在高湿度环境下工作的高性能TENGs仍然是一个巨大的挑战

Benefits of technology

[0014]本发明使用两种不同的导体作为摩擦层材料和电极;通过面对面的方式,构成垂直接触模式的导体摩擦纳米发电机。由于两个导体的摩擦电层之间的态密度匹配,其中使用铜/PEDOT:PSS作为典型制作的摩擦纳米发电机,该发电机可获得1400 V的开路电压和1333 mA m-2的超高电流密度。与传统的介电TENGs相比,其电流密度增加了近三个数量级。更重要的是,我们的设备可以在高湿度环境下稳定工作,这对传统的TENGs一直是一个很大的挑战。令人惊讶的是,当摩擦电层中含有水滴时,我们的TENG甚至可以表现得很好的电性能。这项工作为构建高性能的TENGs提供了一种新的有效策略,在不久的将来可用于许多实际应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115549515B_ABST
    Figure CN115549515B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a conductor-based triboelectric nanogenerator and application thereof, belongs to the technical field of nano energy, and is used for energy collection. The application uses two different conductors as triboelectric layer materials and electrodes; a conductor triboelectric nanogenerator in a vertical contact mode is formed in a face-to-face mode. Due to the matching of the state density between the triboelectric layers of the two conductors, a triboelectric nanogenerator using copper / PEDOT:PSS as a typical production can obtain an open-circuit voltage of 1400V and an ultrahigh current density of 1333mA m ‑2 Compared with traditional dielectric TENGs, the current density is increased by nearly three orders of magnitude. More importantly, the device of the application can stably work in a high-humidity environment, which has been a great challenge to traditional TENGs. When water droplets are contained in the triboelectric layer, the TENG of the application can even exhibit good electrical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a nano-energy source, specifically to a method for preparing a conductor triboelectric nanogenerator and its application. Background Technology

[0002] Triboelectric nanogenerators (TENGs) utilize the triboelectric effect and electrostatic induction to efficiently convert discrete low-frequency mechanical energy into electrical energy. The triboelectric layer in TENGs is typically composed of dielectric polymers with different electron affinities. In some cases, metals with electron-loss capabilities can also be used as positive triboelectric layers. High output voltages (kV) are commonly achieved in many TENGs; however, the output current is typically low (usually in the μA range). This low output current limits many practical applications of TENGs, particularly in energy harvesting. Theoretically, improving charge transfer between triboelectric layers or shortening the charge transfer time is key to increasing the output current. High output currents have been developed for many sophisticated TENGs. For example, Wang et al. reported achieving 300 mA m in a vacuum by avoiding dielectric breakdown. -2 High current density. Wu et al. combined TENG with transistor-like circuits to achieve 1000 mA m -2 High current density. Although the above strategies can increase the output current of TENGs, the resulting output current is still not high enough due to the complexity of the device structure. Further improving the output current of TENGs, especially those with simpler structures, is crucial.

[0003] Furthermore, the output performance of triboelectric transistors (TENGs) is typically affected by humidity. Generally, in high-humidity environments, the triboelectric effect is significantly hindered due to charge leakage from the triboelectric surface to the air. Therefore, the superior performance of TENGs decreases markedly in high-humidity environments. Improving the humidity impedance of TENGs has been a hot research topic. Some reports suggest improving the stability of TENGs in high-humidity air by making the triboelectric layer hydrophobic through material selection or surface engineering. Utilizing the electrostatic breakdown effect has also improved the stability of TENGs in high-humidity environments. However, designing high-performance TENGs capable of operating in high-humidity environments remains a significant challenge.

[0004] Here, we designed and fabricated a novel TENG using conductive materials as the triboelectric layer and electrodes. This novel TENG has a simple structure, and due to density of states (DOS) matching, its output performance, especially its current density, is the highest among TENGs in contact-separation mode. More interestingly, the C-TENG exhibits excellent tolerance to high humidity conditions. Even when water droplets are present on the triboelectric layer, the C-TENG still maintains good performance. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing and applying a conductor triboelectric nanogenerator with excellent stability under high humidity conditions, high output current, and stable operation under high humidity conditions.

[0006] To address the aforementioned technical problems, the present invention proposes the following technical solution: a method for fabricating a conductor-based triboelectric nanogenerator, using different conductors as friction layer materials and electrodes; the fabricated conductor triboelectric nanogenerator C-TENG uses copper and PEDOT:PSS (a conductor polymer material) or aluminum and PEDOT:PSS as the positive electrode friction material and electrode, and the negative electrode friction material and electrode, forming a vertical contact mode of conductor triboelectric nanogenerator through face-to-face contact, thereby obtaining a large current signal.

[0007] Preferably, the size of the friction layer in the specific triboelectric nanogenerator is 5×5cm. 2 The pressure is 5N, the frequency is 5Hz, and the spacing is 6mm.

[0008] Preferably, the generator can obtain an open-circuit voltage of 1400 V and a voltage of 1333 mA m. -2 Its ultra-high current density is nearly three orders of magnitude higher than that of traditional dielectric TENGs.

[0009] Preferably, copper is used as the positive electrode friction material and electrode, and PEDOT:PSS is used as the negative electrode friction material and electrode.

[0010] To solve the above-mentioned technical problems, the technical solution proposed by this invention is: C-TENG can be used for energy conversion and driving electric equipment.

[0011] Preferably, C-TENG is used as an energy harvester to collect energy from various mechanical motions.

[0012] Preferably, using C-TENG to power the calculator watch will enable it to function properly.

[0013] Preferably, low-power electronic devices are driven by connecting the C-TENG to a commercial bridge rectifier and capacitor. Beneficial effects

[0014] This invention uses two different conductors as triboelectric layer materials and electrodes; a conductor triboelectric nanogenerator is constructed in a vertical contact mode by means of face-to-face contact. Due to the density of states matching between the triboelectric layers of the two conductors, where copper / PEDOT:PSS is used as a typical fabricated triboelectric nanogenerator, this generator can achieve an open-circuit voltage of 1400 V and a voltage of 1333 mA m. -2The device achieves an ultra-high current density, nearly three orders of magnitude higher than conventional dielectric TENGs. More importantly, our device can operate stably in high humidity environments, a significant challenge for traditional TENGs. Surprisingly, our TENG even exhibits good electrical performance when water droplets are present in the triboelectric layer. This work provides a new and effective strategy for constructing high-performance TENGs, which can be used in many practical applications in the near future.

[0015] By utilizing a conductive material as both the triboelectric layer and the electrode, this novel TENG expands upon the traditional strategy of using polymer materials as the triboelectric layer. This new TENG structure is simple, and its output performance, especially its current density, is the highest among TENGs in contact-separation mode. We further analyzed the reasons for its superior performance using density of states (DOS). More importantly, this C-TENG exhibits excellent stability in high-humidity environments. Even with water droplets present on the triboelectric layer, the C-TENG still maintains good performance. This invention provides a promising method for fabricating TENG devices with high output current and stability in high-humidity environments. Attached Figure Description

[0016] Figure 1 Design concept and output performance of C-TENG. (a) Density of states matching between three triboelectric couples: dielectric-dielectric, conductor-dielectric, conductor-conductor; (b) Surface potentials of Al, paper, Cu, PEDOT, PSS, PET, PI, PDMS and PTFE; TENGs based on various triboelectric couples (size = 3×3cm) 2 Output (c) voltage and (d) current; (e) comparison with TENG current density in the previously reported vertical contact separation mode.

[0017] Figure 2 The diagram shows the effects of (a) size, (b) pressure, (c) frequency, and (d) spacing on the electrical properties of the C-TENG.

[0018] Figure 3 The stability and moisture resistance of C-TENG. (a) Under 30% relative humidity (RH) conditions, the current of C-TENG remained essentially constant after 10,000 cycles of operation. (b) Under 30% RH conditions, C-TENG maintained high stability for one week. (c) Photograph of a glove box with controlled humidity. (d) When RH is 10%-100%, the voltage and current of conventional dielectric materials drop sharply. (e) When RH is in the range of 10%-100%, the voltage and current of C-TENG remain stable.

[0019] Figure 4The electrical performance stability of C-TENG and conventional dielectric TENG affected by water droplets. (ab) Schematic diagram of C-TENG and dielectric TENG affected by water droplets. (cd) Output voltage and current of C-TENG in dry and wet conditions. (ef) Output voltage and current of dielectric TENG in dry and wet conditions. (gh) Schematic diagram of charge leakage in dielectric TENG and suppression of charge leakage in C-TENG.

[0020] Figure 5 Applications of C-TENG as an energy source. (a) Output voltage and current of C-TENG under different external load resistances. Operating frequency controlled at 5Hz, applied force controlled at 5N. (b) Power density of C-TENG and dielectric TENG under different external load resistances. (cd) Using C-TENG in a 5×5cm... 2 It powers approximately 750 LEDs in a small size. (e) Voltage response curves of the C-TENG when charged with capacitors of 1, 4.4, 10, 100, and 470 μF. (f) Photograph of a commercial calculator powered by the C-TENG. Detailed Implementation

[0021] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. Example 1

[0022] When two triboelectric layers come into contact, electrons from the material with the higher Fermi level will transfer to the material with the lower Fermi level until the new Fermi levels of the two materials become the same. When the triboelectric layer is composed of a dielectric material, a small change in surface charge density can cause a large change in the Fermi level located in the band gap. In contrast, changes in the Fermi level of conductors are much less sensitive to surface charge density because their density of states (DOS) is typically higher near the Fermi level. Figure 1 (a) Therefore, when two dielectric materials are used as triboelectric pairs, the amount of charge transfer is typically small because a small amount of charge transfer is sufficient to balance their Fermi levels. Consequently, the output current of the corresponding TENG is low. For a TENG composed of a combination of dielectric and conductive materials, the output current remains low because, although the conductive material can provide many electrons, the dielectric material cannot accept many. In stark contrast, when a TENG is fabricated using two conductive materials, many electrons need to be transferred to balance their Fermi levels due to the high DOS of both materials near the Fermi level. Therefore, a very high output current is expected. Note that electrostatic induction is negligible in a TENG composed of two conductive triboelectric layers.

[0023] Figure 1Design concept and output performance of C-TENG. (a) Density of states matching between three triboelectric couples: dielectric-dielectric, conductor-dielectric, conductor-conductor. (b) Surface potentials of Al, paper, Cu, PEDOT, PSS, PET, PI, PDMS, and PTFE. Based on various triboelectric couples, TENGs (size = 3 × 3 cm) are presented. 2 (c) Output voltage and (d) current. (e) Comparison with TENG current density in the previously reported vertical contact separation mode.

[0024] We used three types of triboelectric couples: dielectric-dielectric, conductive-dielectric, and conductor-conductor. First, we measured the surface potential of commonly used triboelectric materials, which is closely related to electron affinity (…). Figure 1 (b) Subsequently, dielectric materials with different surface potentials were selected as triboelectric couples, and their output performance was tested. Among the polyimide (PI) / polydimethylsiloxane (PDMS), polyethylene terephthalate (PET) / polytetrafluoroethylene (PTFE), and paper / PTFE couples, the highest open-circuit voltage (V) of the paper / PTFE couple was determined. OC The voltage is 312V, and the maximum short-circuit current (I) is... SC ) is 2.8µA ( Figure 1 (cd in the text). Next, we measured the output performance of TENGs composed of dielectric and conductive materials. For the Cu / PTFE pair, V... OC and I SC The values ​​are all slightly lower than those of the paper / PTFE pair, due to the small difference in electronegativity between Cu and PTFE. In stark contrast, when the triboelectric layers are all composed of conductive materials, their output performance, especially the short-circuit current, is significantly improved. This invention uses copper, aluminum (Al), and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) (PEDOT:PSS, a conductive polymer) as triboelectric materials.

[0025] It is worth noting that the surface potential differences between Cu and Al, Cu and PEDOT:PSS, and Al and PEDOT:PSS are much smaller than those between paper / PTFE pairs. However, for 3×3 cm⁻¹... 2 The Cu / PEDOT:PSS and Al / PEDOT:PSS TENGs achieved an output voltage of ~1000 V and a current of ~1200 μA, which is approximately three orders of magnitude higher than TENGs composed of dielectric / dielectric and dielectric / conductor pairs. This value is significantly greater than that of conventional TENGs composed of dielectric / dielectric and dielectric / conductor pairs. For better comparison with other works, we normalized the short-circuit current, obtaining a current density of 1333 mA m. -2This current density is 55 times higher than the highest current density of other vertical contact mode TENGs. Figure 1 (e in the text).

[0026] Comparative Experiment 1: Different Sizes ( Figure 2 ) Sizes from 1*1cm 2 Increased to 5*5cm 2 The voltage increased from 500V to 1400V; the current increased from 900μA to 2000μA. As the size of the friction layer increased, the total charge transferred between the two friction layers increased, thus improving the electrical performance.

[0027] By making 3 sizes of length * width (1*1cm) 2 3*3cm 2 5*5cm 2 The voltages were 500V, 900V, and 1400V; the currents were 900μA, 1200μA, and 2000μA. With increasing size, both voltage and current increased linearly. Figure 2 (a) in the middle.

[0028] Comparative Experiment 2: Different Pressures.

[0029] We made a 5*5cm size 2 For devices where the applied pressure increases from 1N to 5N, the voltage increases from 500V to 1400V, and the current increases from 700μA to 2000μA, the contact area between the two friction layers (copper foil and PEDOT:PSS) also increases with the increase in pressure, leading to an increase in voltage and current. Figure 2 (b) in the middle.

[0030] Comparative Experiment 3: Different frequencies.

[0031] When the operating frequency increases from 1Hz to 5Hz, the output voltage stabilizes at 1400V, and the current increases linearly from 800μA to 2000μA. Figure 2 (c) The increase in frequency leads to an increase in charge transfer, which well explains the increase in output current.

[0032] Comparative Experiment 4: Different Spacing.

[0033] The initial separation distance between the two triboelectric layers also affects the output performance of the C-TENG. When the initial separation distance is approximately 6 mm, the maximum values ​​of the voltage and current are 1400 V and 2000 μA, respectively. Figure 2(d) From the initial separation distance between 2mm and 6mm, as the distance increases, the electrostatic induction between the two friction layers increases, thus increasing the electrical performance, and the output voltage and current should increase linearly; however, as the initial separation distance further increases from 6mm, the excessive distance between the two friction layers will suppress the electrostatic induction phenomenon, thereby suppressing charge transfer and resulting in a weakening of the electrical performance.

[0034] Figure 2 Optimization of C-TENG output performance. (a) Voltage and current increase with increasing friction layer size. (b) Voltage and current increase with increasing external force. (c) Voltage remains stable, while current increases with increasing operating frequency. (d) With increasing initial separation distance, voltage and current first increase and then decrease, achieving optimal voltage and current at an initial separation distance of 6 mm.

[0035] Figure 3 To improve the electrical stability and moisture resistance of C-TENG.

[0036] (a) Under 30% relative humidity (RH) conditions, the current of C-TENG remained essentially constant after 10,000 cycles of operation. (b) Under 30% RH conditions, C-TENG maintained high stability over one week. (c) Photograph of the glove box with humidity control. (d) When RH is between 10% and 100%, the voltage and current of conventional dielectric materials drop sharply. (e) When RH is in the range of 10% to 100%, the voltage and current of C-TENG remain stable.

[0037] In the following experiment, we used copper as the positive electrode and PEDOT:PSS as the negative electrode and friction material. The device size was selected as 5*5cm. 2 The stability test of the device, such as Figure 3 As shown, our C-TENGs exhibit high stability in cyclic measurements. After 10,000 cycles and 7 days of operation under ambient conditions, the output current of the C-TENGs remained at its initial value ( Figure 3 (a) indicates that C-TENG has excellent electrical performance stability.

[0038] In addition, we chose 1*1cm 2 Humidity stability tests were conducted on the device. The test results showed that, compared to the dielectric material TENG, which exhibits a sharp drop in electrical performance with increasing humidity, this C-TENG also showed high stability in high humidity environments. When the relative humidity increased from 10% to 100%, the voltage and current remained almost unchanged.

[0039] Figure 4 The electrical properties are those of the friction layer surface when water droplets are present.

[0040] In addition to the response to humidity, we will further investigate the effect of water droplets on electrical properties. Figure 4 The electrical performance stability of C-TENG and conventional dielectric TENG affected by water droplets. (ab) Schematic diagram of C-TENG and dielectric TENG affected by water droplets. (cd) Output voltage and current of C-TENG in dry and wet conditions. (ef) Output voltage and current of dielectric TENG in dry and wet conditions. (gh) Schematic diagram of charge leakage in dielectric TENG and suppression of charge leakage in C-TENG.

[0041] like Figure 4 As shown, even with water droplets present between the two friction layers, the C-TENG still exhibits high performance. However, water droplets can be clearly observed on the Cu and PEDOT:PSS surfaces. Figure 4 (ab), we still observed voltages and currents of 350 V and 700 μA, which are approximately 78% and 83% of those under dry conditions (ab). Figure 4 (d) In contrast, we conducted a similar experiment on the dielectric TENG. When water droplets were present in the triboelectric layer, almost no output voltage and current were detected in the dielectric. Figure 4 In high-humidity air, the output performance of TENGs typically decreases significantly due to the leakage of charge from the triboelectric layer into the air. Figure 4 (g in the original text). However, when both triboelectric layers are highly conductive triboelectric layers, charge leakage is suppressed. Electron transfer within a conductive triboelectric layer is much easier than charge leakage from the triboelectric layer to the air. Figure 4 (h in the middle).

[0042] Figure 5 For voltage, current and power under different loads.

[0043] Figure 5 Applications of C-TENG as an energy source. (a) Output voltage and current of C-TENG under different external load resistances. Operating frequency controlled at 5Hz, applied force controlled at 5N. (b) Power density of C-TENG and dielectric TENG under different external load resistances. (c) Voltage response curves of the C-TENG when charged with capacitors of 1, 4.4, 10, 100, and 470μF. (d) Photograph of C-TENG driving a commercial calculator. (e) Using C-TENG in a 5×5cm environment under 30% RH conditions. 2 (f) Powering approximately 750 LEDs in a small size. (f) Using C-TENG at 100% RH in a 5×5cm 2 It powers approximately 600 LEDs in a small size.

[0044] C-TENG can be used for energy conversion and driving electric equipment. For example... Figure 5 As shown in Figure a, we connected our fabricated C-TENG in series with different resistors to test the voltage under different load resistances. The voltage increased as the external resistance decreased from 10... 3 Increase to 10 9 With an output voltage of Ω, the C-TENG increased from 400 V to 1400 V, while the output current decreased from 2.4mA to 2µA. Figure 5 (a) Furthermore, with an external load of 100 kΩ, the maximum power density of this C-TENG is 160 W / m². -2 Compared to traditional TENGs, the maximum power density is 276 times that of traditional TENGs. Figure 5 (b) in the middle.

[0045] By connecting the C-TENG to commercial bridge rectifiers and capacitors, low-power electronic devices can be driven.

[0046] Since the energy generated by triboelectric nanogenerators is in the form of alternating current (AC), a rectifier is needed to convert the AC energy into direct current (DC) to power small electronic devices. The circuit diagram is shown below. Figure 5 As shown in c in the figure.

[0047] The charging capability of capacitors with different capacitances was evaluated using C-TENG. Commercial capacitors with capacitances of 1, 4.4, 10, 100, and 470 µF were charged. Under a light tapping force, a 10 µF capacitor could be charged to 5V in 13 seconds. Figure 5 As shown in c in the figure.

[0048] Using a C-TENG to power the calculator will enable it to function properly, such as... Figure 5 As shown in d.

[0049] This result demonstrates the effectiveness of C-TENG as a device for converting biomechanical energy into electrical energy.

[0050] like Figure 5 As shown, several LED bulbs are connected externally.

[0051] C-TENGs can be used as energy harvesters to collect energy from various mechanical movements. For example... Figure 5 In the case of e, under 30% RH conditions, a 5*5cm object was simply tapped. 2 The C-TENG successfully powered 750 external LED bulbs. More importantly, under 100% RH conditions, the C-TENG was used in a 5*5cm area... 2It powers approximately 600 LEDs in a small size. This result demonstrates that the C-TENG can operate stably in high humidity environments.

[0052] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any way, and all technical solutions obtained by equivalent substitution or equivalent transformation fall within the protection scope of the present invention.

Claims

1. A conductor-based triboelectric nanogenerator, characterized in that... The fabrication method of the conductor-based triboelectric nanogenerator is as follows: Different conductors are used as the triboelectric layer materials and electrodes; the fabricated conductor triboelectric nanogenerator (C-TENG) uses copper and PEDOT:PSS as the positive and negative electrode materials, respectively, forming a vertical contact mode through face-to-face contact; density of states matching is performed between the triboelectric layers of the two conductors; specifically, the size of the triboelectric layer of the triboelectric nanogenerator is 5×5cm. 2 The generator has a pressure of 5 N, a frequency of 5 Hz, and a spacing of 6 mm; it can obtain an open-circuit voltage of 1400 V and a power output of 1333 mA m. -2 The current density.

2. The conductor-based triboelectric nanogenerator according to claim 1, characterized in that: Using copper as the positive electrode and PEDOT:PSS as the negative electrode, this C-TENG expands upon the traditional strategy of using polymer materials as the electrode by utilizing a conductive material as both the friction layer and the electrode. This C-TENG exhibits excellent stability in high humidity environments and maintains good performance even when water droplets are present on the triboelectric layer.

3. The conductor-based triboelectric nanogenerator according to claim 1, characterized in that: C-TENG is used for energy conversion and driving electric equipment.

4. The conductor-based triboelectric nanogenerator according to claim 1, characterized in that: C-TENG is used as an energy harvester to collect energy from various mechanical movements.

5. The conductor-based triboelectric nanogenerator according to claim 1, characterized in that: Power the calculator using a C-TENG to make it work properly.

6. The conductor-based triboelectric nanogenerator according to claim 1, characterized in that: By connecting the C-TENG to commercial bridge rectifiers and capacitors, low-power electronic devices can be driven.

Citation Information

Patent Citations

  • Direct current friction nanometer generator based on organic semiconductor Schottky heterojunction

    CN113746364A